1992
DOI: 10.1203/00006450-199202000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function of Airway Generations 0 to 4 in the Preterm Lamb

Abstract: ABSTRACT. Five generations of airways from 15 pretermPremature airways are highly compliant structures compared lambs of 130-137 d (90% term) gestation were studied to with those of the mature newborn or adult (1-4). This increased investigate the effect of generation on structure-function of compliance can cause airway collapse at negative airway prespreterm airways. Airway rings were measured to determine sures, which results in an increase in resistance to airflow, flow the internal radius (r), and wall thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…It is now generally accepted that bronchoconstriction of such small bronchioles plays an important role in the increase in airway resistance that is elicited by agonists (Moreno et al 1986), and by inference also in asthma. However, although some animal studies have suggested that there may be significant differences in the pharmacological and mechanical function of airways from different parts of the bronchial tree (Fleisch & Calkins, 1976;Fujiwara et al 1988;Gauthier et al 1992;Mustafa et al 1994;Chopra et al 1994Chopra et al , 1997, there have been very few in vitro studies of any type on human small bronchioles. Moreover data obtained from non-human species may not necessarily reflect the situation in human ASM, as we have previously described significant differences between the electrophysiology of ASM from human airways and that of other species (Snetkov et al 1995(Snetkov et al , 1996(Snetkov et al , 1998.…”
Section: Resultsmentioning
confidence: 99%
“…It is now generally accepted that bronchoconstriction of such small bronchioles plays an important role in the increase in airway resistance that is elicited by agonists (Moreno et al 1986), and by inference also in asthma. However, although some animal studies have suggested that there may be significant differences in the pharmacological and mechanical function of airways from different parts of the bronchial tree (Fleisch & Calkins, 1976;Fujiwara et al 1988;Gauthier et al 1992;Mustafa et al 1994;Chopra et al 1994Chopra et al , 1997, there have been very few in vitro studies of any type on human small bronchioles. Moreover data obtained from non-human species may not necessarily reflect the situation in human ASM, as we have previously described significant differences between the electrophysiology of ASM from human airways and that of other species (Snetkov et al 1995(Snetkov et al , 1996(Snetkov et al , 1998.…”
Section: Resultsmentioning
confidence: 99%
“…This may have important consequences, as signi®cant pharmacological and mechanical di erences have been reported between airways from di erent parts of the bronchial tree (Gauthier et al, 1992;Mustafa et al, 1994), including our own studies on small bronchioles of the rat (Chopra et al, 1994;1997). Moreover we have demonstrated that the electrophysiology of human ASM di ers from other species commonly used in airways research (Snetkov et al, 1995;, and more recently that ASM from human small bronchioles (51 mm i.d.)…”
Section: Introductionmentioning
confidence: 88%
“…Differences in the forcefulness of smooth muscle contraction have also been noted between the trachea (zero generation) and fourth generation airways in the tracheobronchial tree in premature sheep (37). The degree of passive, active and total stress that developed decreased significantly as a function of airway level, from highest in the trachea to lowest in the subsegmental bronchi (fourth generation).…”
Section: Level In the Tracheobronchial Treementioning
confidence: 96%